Improved Pore-Size Analysis of Carbonaceous Adsorbents - J. Choma; M. Jaroniec; M. Kloske (Adsorption Science & Technology)
An improvement was proposed for the pore-size analysis of active carbons based on low-temperature (77 K) nitrogen adsorption isotherms measured over a wide range of relative pressures (5 × 10 −7 –0.995). It was shown that the applicability of the Barrett, Joyner and Halenda (BJH) computational method based on the Kelvin equation could be extended significantly towards small mesopores and large micropores when a proper t-curve was used to represent the film thickness of nitrogen adsorbed on the carbon surface. It was proposed that the aforementioned t-curve be obtained from the nitrogen adsorption isotherm at 77 K on a macroporous carbon black by fitting its multilayer part to the calibrated t-curve for nitrogen adsorbed at 77 K on a macroporous silica. To date, the Harkins–Jura or Halsey t-curves have been used to describe the pressure-dependence of the film thickness. This appears to be inaccurate, especially in the range of low relative pressures. It was shown that this inaccuracy makes the pore-size analysis questionable. However, the t-curve proposed in this work gave the pore-size distribution functions for the carbons studied thereby reproducing the total pore volume and showing realistic behaviour in the range at the borderline between micropores and mesopores.